ARDS (Acute Respiratory Distress Syndrome) in Pediatric and Adult - Zulfa Hasyimiyyah Ihtisyam; Latifah Mukhlisatunnafsi; M. Fardi Anugrah; Moon Fahira; Putu Diwyandaani Priyahita; Theophany Margareta Kurniawan; Moulid Hidayat (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Acute Respiratory Distress Syndrome (ARDS) is a serious medical condition that occurs when lungs become severely inflamed, which inhibits the ability to take in the oxygen and eliminate carbon dioxide. The purpose of this article is to find out more about the clinical manifestation, pathophysiology, diagnosis, and treatment of ARDS. The literatures that used for this literature review are from National Center for Biotechnology Information (NCBI), Google scholar, and Proquest. The result for this literature review is the development of ARDS is associated with inflammation in lung’s epithelium, endothelium, and interstitium which consist three phases which is exudative, proliferative, and fibrotic phases. The Berlin Criteria issued by the American-European Consensus Conference (AECC) in 2021 used for ARDS diagnosis. The treatments for ARDS could used pharmacotherapy and non-pharmacotherapy.